The study of school-in-hospital in pediatric wards for children with medical needs in Malaysia - Mat So'od, Noor Fatehah; Abdullah, Fadzidah (2012)
The concept of providing special education services to the children with medical needs is relatively a new project in Malaysia. The study found that during children’s recovering process in any medical centre, their education should not be overlooked as the hospitalized children and young people still need learning activities to maintain a sense of normality in the hospital environment. This study is aimed to investigate spatial requirement to prevent hospitalized children from lagging behind in their studies while undergoing long treatment in hospitals. The lessons must be addressed while the children are under treatments, as it influences the children’s academic future. Bevertheless, this study focuses on examining spatial requirements of existing schools in hospitals, in Malaysia. The study finds that the educational place for the children should be provided based on their age ranges which are preschool, primary school, and secondary school, to fulfill the children’s needs of continuous lessons. Overall, this paper intends to highlight the needs of proper learning place and spatial requirements for future improvement to the existing school in hospital for the education of children with medical needs in Malaysia.